A systematic review on the effects of media disclaimers on young women's body image and mood. (March 2020) - McComb, Sarah E.; Mills, Jennifer S.
Highlights: Disclaimers were ineffective at mitigating women's negative body image after exposure to thin images. Disclaimers were ineffective at mitigating women's negative affect after exposure to thin images. Disclaimers heightened body dissatisfaction in at-risk women. Specific and warning disclaimers were the most harmful to at-risk women's body image. Abstract: The purpose of this systematic review was to determine the effectiveness of media disclaimers in protecting women's body image and mood after exposure to thin ideal media. The keywords "warning*" OR "disclaimer*" AND "body image" OR "body dissatisfaction" were searched in the PsycINFO and MEDLINE/PubMed databases. Inclusion criteria included being a peer-reviewed, primary source article available in English, which had examined the impact of media disclaimers on women's body image. Articles published prior to February 22 nd, 2019 were included. In total, 15 experimental studies were included. Overall, disclaimers were ineffective at reducing women's body dissatisfaction and negative affect following exposure to thin ideal images, and in some cases were actually harmful to women's body image. For women high in trait body dissatisfaction and thin ideal internalization, warning labels increased body dissatisfaction after exposure to thin ideal images. For women high in trait social and appearance comparison specific disclaimers that outlined how the images had been altered resulted in increased body dissatisfaction after exposure to thin ideal images. Therefore, overall, disclaimers were ineffective at ameliorating the negative effects of exposure to thin ideal media. Future research should examine the impact of media disclaimers on the body image of adolescents and men.